2016
DOI: 10.4238/gmr.15027818
|View full text |Cite
|
Sign up to set email alerts
|

Variation in cassava germplasm for tolerance to post-harvest physiological deterioration

Abstract: ABSTRACT. Tolerant varieties can effectively control post-harvest physiological deterioration (PPD) of cassava, although knowledge on the genetic variability and inheritance of this trait is needed. The objective of this study was to estimate genetic parameters and identify sources of tolerance to PPD and their stability in cassava accessions. Roots from 418 cassava accessions, grown in four independent experiments, were evaluated for PPD tolerance 0, 2, 5, and 10 days post-harvest. Data were transformed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…These data demonstrate the possibility of selecting more tolerant genotypes to postharvest physiological deterioration, in accordance with the results obtained by Morante et al (2010). Eucalipto was one of 418 genotypes evaluated by Venturini et al (2016), who also identified it as one of the most tolerant to PPD.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These data demonstrate the possibility of selecting more tolerant genotypes to postharvest physiological deterioration, in accordance with the results obtained by Morante et al (2010). Eucalipto was one of 418 genotypes evaluated by Venturini et al (2016), who also identified it as one of the most tolerant to PPD.…”
Section: Resultssupporting
confidence: 88%
“…There is a wide variation for symptoms of postharvest physiological deterioration (PPD) even among roots from the same genotype, making the interpretation of the results difficult. For this reason, Venturini et al (2016) proposed to express this trait in terms of the area under the deterioration progress curve (AUDPC), an adaptation of the concept of area under the disease progress curve (CAMPBELL; MADDEN, 1990). The values for area under the deterioration progress curve (AUDPC) were classified into two groups.…”
Section: Resultsmentioning
confidence: 99%
“…In Indonesia, different cassava genotypes were observed to have a range of 10 to more than 20% deterioration and were classified as having low, medium, and high susceptibility to PPD [51]. Similar variations have also been observed in cassava from Africa and South America [52][53][54]. The genes responsible for PPD and the associated quantitative trait loci (QTLs) have already been mapped in the cassava genome [55,56].…”
Section: Improvement Of Cassava Against Post-harvest Physiological De...mentioning
confidence: 85%
“…Cassava cultivars that accumulate hydroxycoumarins are susceptible to PPD [ 5 ], so an alternative approach for delaying PPD in cassava is to breed varieties with lower hydroxycoumarin contents. Favorable trait segregation and high heterozygosity in the cassava genome constrain the screening progress of preferential varieties with PPD tolerance [ 32 ] and traditional hybridization breeding. In recent years, there has been more success in using transgenes to decrease the contents of scopoletin and scopolin; examples include ectopic expression of HEWL to inhibit PPO activity and silencing of the expression of F6′H in cassava [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Favorable trait segregation and high heterozygosity in the cassava genome constrain the screening progress of preferential varieties with PPD tolerance [ 32 ] and traditional hybridization breeding. In recent years, there has been more success in using transgenes to decrease the contents of scopoletin and scopolin; examples include ectopic expression of HEWL to inhibit PPO activity and silencing of the expression of F6′H in cassava [ 31 , 32 ]. C3′H is considered to be a key enzyme for the synthesis of scopoletin and scopolin in plants [ 16 , 33 ].…”
Section: Discussionmentioning
confidence: 99%